STUDYING ABROAD: MALAY STUDENTS ATTITUDE TOWARDS THE UK EDUCATION SYSTEM AND PERSONAL ADJUSTMENTSTUDYING ABROAD: MALAY STUDENTS ATTITUDE TOWARDS THE UK EDUCATION SYSTEM AND PERSONAL ADJUSTMENT - Rashidah Mamat; Nor Azlah Sham Rambely (Proceedings of The ICECRS, 2016)
The Malaysian government is concerned about the significance of studying abroad and has therefore been very active in sending students abroad to study. Malaysia has an elaborate foreign scholarship program which sees 10,000 or more students relocate abroad annually and the majority of them are Malays or Bumiputera. Studying abroad is seen as a backbone to produce a potential citizen that functions effectively in society and plays a role in economic and national development. This paper provides an analysis of Malay undergraduate students’ narratives of their perceptions and attitudes towards studying abroad and the UK’s education system. The purpose of this paper is to investigate, share and understand their process of adjustment and adaptation as well as the challenges they encounter while abroad. The findings support the previous literature that studying abroad has a significant impact on the students’ life experience. The problems students encountered as being of three general types: socio-cultural adjustments; language issues; and learning and teaching approach. It is argued here that these experiences and problems, along with other aspects of their previous education system, interaction with the locals/ host national, religion, culture and language, had an influence on their attitudes towards study in the UK.